2005
DOI: 10.1111/j.1439-0523.2005.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

The high and low molecular weight glutenin subunit polymorphism of Algerian durum wheat landraces and old cultivars

Abstract: The high molecular weight (HMW) and B-zone low molecular weight (B-LMW) glutenin subunit composition of 45 Algerian durum wheat (Triticum turgidum L. var. durum) landraces and old cultivars were examined by sodium-dodecyl-sulphate polyacrylamide gel electrophoresis (SDS-PAGE). Nine accessions were heterogeneous and presented two or three genotypes. All together, 33 glutenin patterns were detected, including 12 for HMW and 15 for B-LMW glutenin subunits. Twenty-four different alleles were identified for the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 18 publications
13
32
2
2
Order By: Relevance
“…In agreement with previous studies (Liu and Shepherd 1996;Cherdouh et al 2005), cluster analysis grouped MC with genotypes from Italy and the three Maghreb countries due to the high frequency of LMW models type 2. A second group clustered countries in which LMW-2 models were found from medium to low frequencies (Turkey, Jordan, Lebanon, Portugal and Spain), while a third branch joined 12 countries in which LMW-2 models were absent.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In agreement with previous studies (Liu and Shepherd 1996;Cherdouh et al 2005), cluster analysis grouped MC with genotypes from Italy and the three Maghreb countries due to the high frequency of LMW models type 2. A second group clustered countries in which LMW-2 models were found from medium to low frequencies (Turkey, Jordan, Lebanon, Portugal and Spain), while a third branch joined 12 countries in which LMW-2 models were absent.…”
Section: Discussionsupporting
confidence: 75%
“…This diversity is substantially greater than reported by previous studies conducted in durum wheat (Turchetta et al 1995;Cherdouh et al 2005;Moragues et al 2006c). The considerable variability of glutenin combinations found in LR can potentially enhance their value in breeding to broaden the genetic basis of gluten quality improvement, beyond what can be achieved by using modern germplasm.…”
Section: Discussioncontrasting
confidence: 47%
“…A total of 17 alleles were identified (Table 4). The identified low molecular weight glutenin subunits were those previously described by Nieto-Taladriz et al (1997), except subunit 8+ encoded by the allele Glu-A3j, which was identified by Cherdouh et al (2005). The most common allele at Glu-A3 was Glu-A3c encoding subunits 6+10 with a frequency of 26.67%, followed by Glu-A3b encoding subunit 5 at 23.33%.…”
Section: Allelic Diversity Of Glutenins In Saharan Wheatsmentioning
confidence: 99%
“…The availability of such germplasm depends on the identification of the sources of diversification (Devra, 1999), especially within the primary and secondary diversity centres which are characterised by large diversity. The local germplasm is adapted to a wide range of environments and carry a large reservoir of useful genes (Asfaw, 1989;Cherdouh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%